2021
DOI: 10.4081/memoriesei.2020.261
|View full text |Cite
|
Sign up to set email alerts
|

Updated knowledge on Italian Dermaptera with the report of a new alien species: <em>Forficula smyrnensis</em> Audinet-Serville, 1838

Abstract: The Dermaptera species number reported for the Italian fauna (27 species) is the most conspicuous among the European Union. The knowledge on Italian Dermaptera is among the most accurate in Europe, above all thanks to the large number of well-known entomologists who, over two centuries, have dedicated themselves to it in depth. Half of the species of Dermaptera known for Italy have indeed been described by Italian entomologists. Four species are alien and some of which have long been acclimatized in Italy. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, it is important to note that about 40% of the native earwig fauna of Italy (including Sicily, Corsica, and Sardinia) is endemic to this area (and this proportion would be even higher considering that the distribution of Chelidurella pseudovignai Kočárek & Kirstová, 2020 and C. mutica (Krauss, 1886) out of Italy is restricted to areas close to the borders of the study area), and relatively high proportions of the endemic species are found in most of the regions. The earwigs endemic to Italy can be classified into two main groups whose distributions correspond to the two main mountain ranges: the Alpine endemics ( Chelidura aptera (Megerle in Charpentier, 1825), Chelidurella poggii Capra, 1982, and C. vignai Galvagni, 1995) and the Apennine endemics ( Chelidurella caprai Vigna Taglianti, 1993, Pseudochelidura galvagnii Vigna Taglianti, 1999, P. orsinii (Gené, 1833), Forficula apennina Costa, 1881, and Forficula silana Costa, 1881) [ 4 , 8 ], which is consistent with the recognized importance of mountain ranges for cladogenetic processes in these animals in Europe [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to note that about 40% of the native earwig fauna of Italy (including Sicily, Corsica, and Sardinia) is endemic to this area (and this proportion would be even higher considering that the distribution of Chelidurella pseudovignai Kočárek & Kirstová, 2020 and C. mutica (Krauss, 1886) out of Italy is restricted to areas close to the borders of the study area), and relatively high proportions of the endemic species are found in most of the regions. The earwigs endemic to Italy can be classified into two main groups whose distributions correspond to the two main mountain ranges: the Alpine endemics ( Chelidura aptera (Megerle in Charpentier, 1825), Chelidurella poggii Capra, 1982, and C. vignai Galvagni, 1995) and the Apennine endemics ( Chelidurella caprai Vigna Taglianti, 1993, Pseudochelidura galvagnii Vigna Taglianti, 1999, P. orsinii (Gené, 1833), Forficula apennina Costa, 1881, and Forficula silana Costa, 1881) [ 4 , 8 ], which is consistent with the recognized importance of mountain ranges for cladogenetic processes in these animals in Europe [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy was according to Fontana et al [ 4 ]. A matrix of species presence/absence in each geographical region and adjacent areas ( Table S1 ) was compiled by assembling data from literature sources [ 4 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 54 , 55 , 56 , 57 , 58 ]. Introduced species were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most species-rich among these genera, Pseudochelidura, endemic to Italy, France, Andorra, and Spain, was considered to include five species: P. sinuata (Germar, 1825), P. minor Steinmann, 1979, P. montuosa Steinmann, 1981, P. galvagnii Vigna Taglianti, 1999 (Gené, 1833) (Steinmann 1981;Herrera-Mesa 1999;Fontana et al 2021a). The high elevation areas of the Pyrenean mountains, lying between France and Spain, are thought to be inhabited by three species of Pseudochelidura, one of them, P. montuosa, considered extremely rare (Steinmann 1981;Caussanel et al 1990;Cuesta-Segura 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The small number of reported alien Dermaptera could be related to both their low species richness as well as their cryptic nature. Until now, only two alien earwigs have been recorded from Greece, namely Euborellia femoralis (Dohrn, 1863) and Forficula lucasi Dohrn, 1865 raising the Greek earwig fauna to 18 species (Haas 2015(Haas , 2018Demetriou et al www.entsoc.gr © 2022Hellenic Entomological Society 2021Fontana et al 2021;Zafeiriou et al 2021;Kalaentzis et al 2022).…”
Section: Introductionmentioning
confidence: 99%